La calidad del empleo en Argentina durante la posconvertibilidad: Propuesta metodológica y análisis de indicadores de segmentación laboral - Giosa Zuazua, Noemí (2020)
This article has two main objectives. In the first place, we aim to explore the potential of the Argentine economy to generate employment and to absorb the surpluses of workforce during the 2000s. To do this, it is necessary to analyze the problem of labor informality in a wide sense. The second aim is to propose a set of indicators for the measurement and analysis of labor segmentation, which include the identification and evolution of surpluses of workforce and of the quality of paid/wage-earning employment. The debates on these issues carried out in Latin America from the 50s until the present are discussed, and the key aspects to distinguish and quantify employment strata are identified. The results suggest that even though there have been generalized improvements in the conditions of employment, the participation of each type of employment has not changed.